Impediments to study sports activities for government universities in Baghdad - Hussein, Eman; Mohameed, Hoda (Journal of Physical Education, 2014)
Search included five sections are :: Part I: research and definition of this section includes Introduction of research and its importance: The University is an educational institution achieve the full development of students of all aspects of mental and psychological, social, and therefore the student activity, especially sports activity occupies a particularly important programs of universities through the preparation and implementation of sports programs according to the scheduling, where contribute to these programs in guiding students to take advantage of leisure exploited positively useful and achieve cross-cutting elements for the growth of the students developed an integrated both physically and health or psychologically, socially, and in spite of the importance and However, there is a weakness in student participation in sports activities so research aims to identify the obstacles to such activities and student participation in and reasons for the poor participation from their point of view. Part II: theoretical studies and similar: contains the section on theoretical studies related to the research, which included basic concepts of sports activity in general and sports activity university in particular, and the strategy upon which to build the foundations of sports activities in the universities as well as previous studies and similar, discuss and comment on them and draw benefit from them. Part III: research methodology and procedures of the field: This included the door research methodology and procedures of the field, the researcher used the descriptive style survey of its relevance to the research problem, and steps to perform the search, which included access to sources of Arab and foreign countries and conduct personal interviews with experts and specialists to identify themes and then addressed to the community and a sample Search of college students covered by the research and study of the morning for the academic year (2012 - 2013) and numbered (1011) students representing 5% of the community of origin and design of the questionnaire and extract the coefficients of validity and reliability, objectivity and tools and devices used and then experiment reconnaissance and then experience the main as well as the means of statistical used in the search. Part IV: Results, analysis and discussion of eating display and analysis of research data and discuss the use of appropriate statistical methods in order to achieve the objectives of the research Part V: Conclusions and Recommendations: researcher in the study to the most important conclusions and recommendations